2006
DOI: 10.1128/aac.00943-05
|View full text |Cite
|
Sign up to set email alerts
|

Population Analysis of Weight-, Age-, and Sex-Related Differences in the Pharmacokinetics of Lopinavir in Children from Birth to 18 Years

Abstract: The pharmacokinetics of lopinavir were investigated by the use of a population approach performed with the nonlinear mixed effect modeling program NONMEM and 157 children ranging in age from 3 days to 18 years. The pharmacokinetics of lopinavir were well described by a one-compartment model in which the absorption and the elimination rate constants were equal. Typical population estimates of the apparent volume of distribution (V/F) and plasma clearance (CL/F) were 24.6 liters and 2.58 liters/h, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
27
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 31 publications
7
27
1
Order By: Relevance
“…The actual administered doses were as high as 433 mg/m 2 (14.8 mg/kg) and 487 mg/m 2 (17.4 mg/kg) in group 1 and group 2, respectively, which were well tolerated by study subjects. While we found an NNRTI effect on LPV CL similar to that suggested by prior studies (17), our study did not show the age and gender difference in CL identified by those investigators, perhaps because of the small size of this cohort.…”
Section: Discussionsupporting
confidence: 62%
“…The actual administered doses were as high as 433 mg/m 2 (14.8 mg/kg) and 487 mg/m 2 (17.4 mg/kg) in group 1 and group 2, respectively, which were well tolerated by study subjects. While we found an NNRTI effect on LPV CL similar to that suggested by prior studies (17), our study did not show the age and gender difference in CL identified by those investigators, perhaps because of the small size of this cohort.…”
Section: Discussionsupporting
confidence: 62%
“…For each sampling, the drug dosing regimen, the time from the last dosing, body weight, post-natal age (PNA),gestational age (GA) and combined treatments were recorded. The assays for lopinavir were performed on four different sites: site 1 Saint Vincent de Paul Paris; site 2 UK sites;site 3 Hopital Tenon Paris;site 4,Marseille,according to validated HPLC methods [4]. The quantification limit of the method was 0.05 mg l -1 , the inter-assay precision and bias being 7% in the calibration range of 0.1-20 mg l -1 .…”
Section: Methodsmentioning
confidence: 99%
“…The quantification limit of the method was 0.05 mg/liter according to a validated method (12). The determination of HIV RNA levels, or viral loads, in blood samples was performed with a Roche COBAS AmpliPrep/COBAS TaqMan HIV-1 test, with a limit of quantification (LOQ) of 50 copies/ml.…”
Section: Methodsmentioning
confidence: 99%